Islamic Religion Pattern In Farmers’ Families At Dusun Kwagean Desa Krenceng Kecamatan Kepung Kabupaten Kediri - Ulfatu Tahlia; Makhfud Makhfud (eL Bidayah: Journal of Islamic Elementary Education, 2019)
Parents are fully responsible for providing Islamic religious education to children. This attitude can be seen from including the way parents give treatment to children, how to give gifts and punishments, how parents give attention and respond to desires child. With the right pattern of Islamic education there is a possibility that Islamic religious education will succeed in the family so that it can give birth to the expected generation. The researcher takes a focus on the problem, namel The Pattern of Islamic Education for Children in Farmers' Families in the Kwagean Hamlet of Krenceng Village, Kepung District, Kediri Regency. This research is type kualitatif research. Besides that ini collect author data use method observation, interview and documentation. The results of this study are Farmers' families in Krenceng Village in educating their children use several methods, namely training / habituation methods, exemplary methods and advice / ibrah and maudloh methods. The pattern of Islamic religious education used by the farmer's family in educating their children consists namely; Authoritative education patterns, Authoritarian education patterns, and Permissive education patterns.